Analisis Pentingnya Meningkatkan Pengetahuan Akan Dasar-Dasar Perpajakan Bagi Generasi Milenial - Dwiki Wardana Syah; Ryan Hidayat; Ridho Ramadiansyah; Lazuardi Yusuf Suharto; Dini Vientiany (Pajak dan Manajemen Keuangan, 2024)
Increasing the level of understanding about taxation for the nation's next generation, namely the millennial generation, is very important to create the next generation who understand and obey taxation in order to realize a bright future for the nation. The qualitative approach method is the research methodology used in this research journal, and the type of research is literature study or also library research where this research method collects data through studying and understanding theories from related literature or different sources. The findings from this research are that it is very important for the millennial generation to be provided with knowledge about the basics of taxation as early as possible, so that the millennial generation can understand how important taxes are for the development of the country